Plasma Adrenomedullin Concentrations in Critically Ill Neonatal Foals. (28th April 2014) - Toth, B.; Slovis, N.M.; Constable, P.D.; Taylor, S.D.
<x xml:space="preserve">Abstract</x> Background Bacterial sepsis remains a leading cause of morbidity and mortality in neonatal foals, but accurate diagnostic and prognostic markers are lacking. Adrenomedullin (AM) is a polypeptide with diverse biologic effects on the cardiovascular system that increases in septic humans and laboratory animals. Hypotheses Plasma AM concentration (p[AM]) is increased in septic neonatal foals compared to sick nonseptic and healthy control foals, and p[AM] is predictive of survival in septic neonatal foals. Animals Ninety critically ill (42 septic, 48 sick nonseptic) and 61 healthy foals <1 week of age. Methods A prospective observational clinical study was performed. Venous blood was collected from critically ill foals at admission and from healthy foals at 24 hours of age. Critically ill foals were categorized as septic or sick nonseptic based on blood culture results and sepsis score. Plasma [AM] was measured by using a commercially available ELISA for horses. Data were analyzed by using the Mann‐Whitney U‐test and P < .05 was considered significant. Results Plasma [AM] was not significantly different between septic and sick nonseptic foals (P = .71), but critically ill foals had significantly increased p[AM] compared to healthy controls (P < .0001). In critically ill foals, p[AM] was not predictive of survival (P = .051). A p[AM] cutoff concentration of 0.041 ng/mL provided a test sensitivity of 91% and specificity of 54% to predict illness. Conclusions and Clinical Relevance Plasma [AM] shows promise as a marker of health in neonatal foals, but p[AM] increases nonspecifically during perinatal illnesses and is not necessarily associated with sepsis.